2018
DOI: 10.2298/gensr1801143n
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between Aspergillus flavus and Aspergillus parasiticus isolates originated from wheat

Abstract: The species of the genus Aspergillus, A. flavus and A. parasiticus, are the most aflatoxin-producing fungi. All previous studies carried out under the production conditions of Serbia showed no presence of A. parasiticus on wheat kernel. On the basis of changes in climatic factors, such as occurrence of high temperatures and prolonged droughts, which favour increased frequency of Aspergillus spp., we assumed that this pathogen can also be present in Serbia. The significance of direct losses as a consequence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Our findings were similar to those reported by ( Kana et al 2013 ), which indicate that all A. flavi isolates recovered from all the commodities (feedstuffs and animal feed) were A. flavus . In contrast, other studies ( Stanković et al 2015 ; Nikolic et al 2018 ) found the presence of A. parasiticus on wheat kernels and corn. This difference may result from the geographic isolation and the local atmosphere conditions (temperature, humidity), which might cause shifts in mycobiota distribution and composition of cereals observed among different regions.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Our findings were similar to those reported by ( Kana et al 2013 ), which indicate that all A. flavi isolates recovered from all the commodities (feedstuffs and animal feed) were A. flavus . In contrast, other studies ( Stanković et al 2015 ; Nikolic et al 2018 ) found the presence of A. parasiticus on wheat kernels and corn. This difference may result from the geographic isolation and the local atmosphere conditions (temperature, humidity), which might cause shifts in mycobiota distribution and composition of cereals observed among different regions.…”
Section: Resultsmentioning
confidence: 76%
“…Previous studies indicated that PCR-IGS-RFLP using restriction enzymes that cleave the PCR products into sub-fragments are valuable tools for detecting and differentiating between A. flavus and A. parasiticus (El Khoury et al 2011;Nikolic et al 2018;Lavkor 2020). Therefore, we used the restriction endonuclease BglII to digest the four PCR products.…”
Section: Resultsmentioning
confidence: 99%
“…Certain mycotoxins can defeat the immune system (BENNETT and KLICH, 2003), thereby exposing the consumer to serious health threats. In Serbia aflatoxins have been detected in high levels on the maize kernels, which are secondary metabolites produced by A. flavus and A. parasiticus (KOS et al, 2018;NIKOLIĆ et al, 2018;OBRADOVIĆ et al, 2018). Fumonisins produced mainly of F. verticillioides and F. proliferatum (Matsush.)…”
Section: Introductionmentioning
confidence: 99%